Le leggi ittite. Con prefazione di G. Pugliese Carratelli - Imparati, Fiorella (1964)
Centro di studi micenei. Università di Roma; ersch. 1965; Transliteration, Translation and Commentary of Hittite Laws, Series I and II; L.it. 6000.